1999
DOI: 10.1080/02724939992527
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid disease of the liver in children

Abstract: Between 1986 and 1997, 21 children (ten boys and 11 girls) had surgery for hydatid disease of the liver. Their mean age was 6.5 years (range 3-12). Abdominal distention with a mass was the commonest presenting symptom (71.4%), followed by abdominal pain (38%). Hepatomegaly with a palpable mass was present in 12 (57%). Three children had concomitant pulmonary and brain hydatid disease. The diagnosis was established clinically and by skin testing, serology and imaging techniques. All patients received a pre-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Eosinophilia was found in 38% of patients, 3 and the rapid Casoni skin test was found to be positive in between 50% 3 and 83% 4 . The most common serological tests include the complement fixation test, the indirect fluorescent antibody test, ELISA and specific immunoelectrophoretogram.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Eosinophilia was found in 38% of patients, 3 and the rapid Casoni skin test was found to be positive in between 50% 3 and 83% 4 . The most common serological tests include the complement fixation test, the indirect fluorescent antibody test, ELISA and specific immunoelectrophoretogram.…”
Section: Discussionmentioning
confidence: 96%
“…Complications of the presence of cysts may include symptoms such as shoulder pain with diaphragmatic irritation, peritonitis, pancreatitis and anaphylaxis with intra‐peritoneal rupture, jaundice and cholangitis with intrahepatic rupture or obstruction, pleural hydatid disease with intrathoracic rupture, or fever and pain with cyst infection and abscess formation. A recent review found that the most common presenting complaint with hydatid disease of the liver is abdominal distension or the finding of an abdominal mass in 15 out of 21 children (71%) 3 . Abdominal pain is often recurrent, or may be acute after blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The middle and dogs. 5 Our patient's parents farmed in a rural area of Turkey and she lived in con-layer, the so-called cuticular membrane, is …”
Section: Introductionmentioning
confidence: 99%
“…8 Cerebral hydatid circulation and involve various abdominal cyst should be kept in mind for the diVerential and extra-abdominal organs. 3,5,6 diagnosis of cystic cranial lesions. In endemic areas, where up to 25% of The hydatid cyst wall has three layers.…”
Section: Introductionmentioning
confidence: 99%